SISTEM INFORMASI MANAJEMEN ASET MENGGUNAKAN METODE DEPRECIATED REPLACEMENT COST DI SATKORDIKCAM JEPARA - Muhammad Alfianto Wisnu Prasetyo; Noor Azizah; Heru Saputro (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Learning support equipment is a very important main component in an educational process, because the learning process uses tools to facilitate the educational process. SATKORDIKCAM is this government agency that regulates education in the sub-district area, so in every sub-district there will be a similar institution, because SATKORDIKCAM controls education in the sub-district area it regulates and has various tasks, one of which is in the field of goods management, namely by fostering, supervising and control the state property owned, and must document and manage the goods in their environment. The documentation process which consists of supervising and controlling the goods is a form of management so that the condition of the goods can be known. The status of the goods or conditions in question include the position of the goods, the condition of the goods, the current price of the goods, and the service life of the goods. Submission of web-based information can make it easier to access information on goods anywhere and anytime online. Making it easier for the admin to carry out the asset management process and the calculation of asset depreciation.